Telaah Respon Lingkungan Sosial Kampus Terhadap Agile Governance dan Zona Integritas di Perguruan Tinggi: An Examination of the Response of the Campus Social Environment to Agile Governance and Integrity Zones in Universities - Prihatini, Evi Nadhifah; Mayarni, Mayarni; As'ari, Hasim; Zulkarnaini, Zulkarnaini; Desiarti, Eka (Anterior Jurnal, 2025)
The implementation of Agile Governance in developing Integrity Zones (ZI) represents a new strategy in higher education bureaucratic reform in Indonesia. This approach emphasizes responsiveness, collaboration, and continuous improvement in institutional governance. However, its success greatly depends on campus social dynamics, particularly how the academic community receives, understands, and executes policies. This article aims to critically examine the social environment's response to implementing Agile Governance within the context of ZI and analyze the relationship between structural policies and organizational culture. This study employs a document analysis method with a descriptive-qualitative approach, focusing on reviewing policy documents, implementation guidelines, and execution reports of ZI and Agile Governance at several Indonesian universities. The findings indicate that successful governance transformation is not solely determined by administrative completeness but is also significantly influenced by the active participation of the academic community, digital technology readiness, and institutional capacity to overcome cultural resistance. Integrating local values, transformative leadership, and institutionalized reflection mechanisms are key factors in internalizing integrity values and agile principles. This article recommends strengthening value-based governance models, enhancing institutional adaptive capacity, and developing participatory ecosystems as core strategies to achieve successful bureaucratic reform in universities through the Agile Governance approach.